Economic and methodological foundations for diagnosing investment and financial risks in construction development under wartime and post-war transformations - KUCHERENKO, Oleksandr; FEDOROV, Vyacheslav; KRUPNYK, Danylo (Ways to Improve Construction Efficiency, 2024)
The article presents a multi-level methodology for the economic diagnosis of investment and financial risks and uncertainty in construction development during wartime and the subsequent recovery period. It traces the evolution of approaches to understanding risk—from classical probabilistic interpretations to modern integrated models that combine econometrics, behavioral economics, and artificial intelligence tools. The authors demonstrate how armed conflict alters the economic parameters of the construction market by constraining lending, increasing currency volatility, disrupting logistics chains, and intensifying inflationary pressure. Legal and political factors manifest themselves in dynamic regulatory changes, the reallocation of state resources, and the need for international guarantees and political-risk insurance. The security dimension creates a constant threat of physical asset loss and necessitates specialized mechanisms of insurance and financial protection. The proposed adaptive risk-management model is conceived as a continuous cycle of “observation – orientation – decision – action – review,” integrating BIM, ERP, and CRM data flows and employing scenario analysis, stress testing, Bayesian networks, and fuzzy logic. Its financial core ensures portfolio allocation of risk capital based on RAROC and CVaR, while the operational level incorporates modular construction, inflation clauses, and flexible IPD-type contract schemes. Particular attention is given to organizational innovations such as cross-functional “risk squads,” rapid risk sprints, and the introduction of the Site Risk Officer role for prompt threat response. The research results form a scientific and applied toolkit for reducing uncertainty and enhancing the investment resilience of construction companies, offering a risk-management roadmap that preserves construction pace and investor confidence in an environment of continuous transformation.